The Study of Synonymous Word "Mistake" - Suwardi, Albertus (Journal of English and Education (JEE), 2009)
This article discusses the synonymous word "mistake*.The discussion will also cover the meaning of 'word' itself. Words can be considered as form whether spoken or written, or alternatively as composite expression, which combine and meaning. Synonymous are different phonological words which have the same or very similar meanings. The synonyms of mistake are error, fault, blunder, slip, slipup, gaffe and inaccuracy. The data is taken from a computer program. The procedure of data collection is by clicking the right mouse on the word mistake. The synonyms of mistake are error, fault, blunder, slip, slipup, gaffe and inaccuracy. The data is taken from a computer program. The procedure of data collection is by clicking the right-mouse on the word. Mistake is the most general and used in most situations.